2014
DOI: 10.3171/2013.9.jns12686
|View full text |Cite
|
Sign up to set email alerts
|

Auditory brainstem implants in neurofibromatosis Type 2: is open speech perception feasible?

Abstract: Object Patients with bilateral auditory nerve destruction may perceive some auditory input with auditory brainstem implants (ABIs). Despite technological developments and trials in new stimulation sites, hearing is very variable and of limited quality. The goal of this study was to identify advantageous and critical factors that influence the quality of auditory function, especially speech perception. Methods The authors conducted a prospective study on ABI operations performed with the aid of multimodality n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 66 publications
0
31
0
6
Order By: Relevance
“…Considering the large number of the affected patients, early diagnosis and treatment of the disease is mandatory in order to achieve favourable results. However, the chances to preserve hearing decrease with increasing tumour size despite advanced surgical techniques and a high percentage of the patients experience severe to profound hearing loss [10][11][12][13] . Therefore, the demand for a sufficient hearing supply after surgical removal is rising.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the large number of the affected patients, early diagnosis and treatment of the disease is mandatory in order to achieve favourable results. However, the chances to preserve hearing decrease with increasing tumour size despite advanced surgical techniques and a high percentage of the patients experience severe to profound hearing loss [10][11][12][13] . Therefore, the demand for a sufficient hearing supply after surgical removal is rising.…”
Section: Introductionmentioning
confidence: 99%
“…The quantity and quality of hearing rehabilitation is increasing from normal hearing aids, cross-and bicross-hearing-systems, bone conducted hearing aids, middle ear implants (MOI), cochlear implantation (CI), auditory brainstem implant (ABI) and auditory midbrain implant (AMI). After surgical removal of VSs, especially in neurofibromatosis type 2 patients, the supply with ABI is in most cases an option, but several studies showed an unsatisfactory outcome 8,11,13,14 . Especially the speech perception with an ABI in adults 15 , compared to the supply in young children 16 , is a huge breakdown.…”
Section: Introductionmentioning
confidence: 99%
“…In only a very small number of individuals was performance with the ABI comparable to that expected from a cochlear implant, most of whom achieve open-set speech understanding and high sentence scores even in NF2 (9). While these results are comparable to the majority of studies evaluating the ABI5 (4,5,(9)(10)(11)(12)(13)(14), some recent publications have demonstrated a greater proportion of high performing users (15)(16)(17)(18). Explaining the discrepancy between outstanding results and limited audition remains the biggest challenge for teams working with the ABI.…”
Section: Discussionmentioning
confidence: 64%
“…They surmised that the effects of preoperative tumor size and surgical removal caused deleterious effects to the cochlear nucleus. More recently Matthies et al (15,16), and Behr et al (17), have demonstrated similar outcomes with NF2 patients as well, finding that tumor size did not affect their results. The two outstanding patients in our series had large tumors with brain stem compression; the best was in a young man presenting with two 4 cm tumors.…”
Section: Preoperative Factors As Prognostic Indicatorsmentioning
confidence: 75%
“…For children suffering from bilateral, ossified cochlea secondary to meningitis, five out of the nine patients experienced a meaningful benefit from ABI, with access to conversational speech and sound field thresholds varying from 25 to 50 dB [8]. Although historically NF2 patients have had exceedingly limited benefit from ABIs due to the detrimental nature of the tumors, more recent studies from Europe have reported considerable success in ABI performance in NF2 patients, including a mean open-set speech perception of 41% at 24 months post-ABI activation in 18 NF2 patients [77]. Notably, a penetrating ABI and an auditory midbrain implant inserted into the inferior colliculus did not lead to an increased benefit over the ABI [69,70,138].…”
Section: Auditory Nucleus and Ganglion Stimulationmentioning
confidence: 92%